Numerical simulation of particle motion characteristics in quantitative seed feeding system - Gao, Xiaojun; Zhou, Zongyan; Xu, Yang; Yu, Yingbo; Su, Yuan; Cui, Tao (Powder technology, 2020)
High-speed precision seed metering device is the key to achieve efficient and precise seed planting in agricultural industry. In this work, a novel quantitative seed feeding system containing a feeding device and a venturi feeding tube is investigated using the coupled CFD and DEM approach. The flow behavior of seed particles and airflow field in this system are analyzed in detail, and the effects of different variables related to venturi tube and operations are examined. The results show that as the nozzle convergence angle increases, the pressure at the nozzle gradually decreases and the pressure gradient extends. As a result, particle movement mobility is enhanced and particle accumulation is reduced. With the increase of the feeding angle, seed particles tend to deposit and collide with the bottom wall. The results also show that when wind pressure reaches above 10 kPa, the spacing between two adjacent seed particles is more consistent, and seed particles are more uniformly discharged from the venturi tube. The results demonstrate that for a better design of the quantitative seed feeding system, the proper nozzle convergence angle is roughly at 70°, and the feeding angle is at around 45° [Display omitted] •CFD-DEM is used to optimize a novel seed feeding system parameters.•Seed particles can flow evenly in a grid groove seed supply wheel.•Feeding convergence angle of 70° shows relatively uniform gas and particle flow.•Feeding angle at 45° gives more smooth entry of particles to nozzle.•Wind pressure affects discharged particle positions and uniformity significantly.